2018
DOI: 10.1002/mgg3.404
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the age of Hb G‐Coushatta [β22(B4)Glu→Ala] mutation by haplotypes of β‐globin gene cluster in Denizli, Turkey

Abstract: BackgroundHb G‐Coushatta variant was reported from various populations’ parts of the world such as Thai, Korea, Algeria, Thailand, China, Japan and Turkey. In our study, we aimed to discuss the possible historical relationships of the Hb G‐Coushatta mutation with the possible migration routes of the world. For this purpose, associated haplotypes were determined using polymorphic loci in the beta globin gene cluster of hemoglobin G‐Coushatta and normal populations in Denizli, Turkey.MethodsWe performed statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Hb G-Coushatta data associated with the [− + − + + + +] haplotype in Denizli, Türkiye have been published [4,29]. It has been reported that the Hb G-Coushatta cases in this region date back to 38,000 ybp [30]. Similar to Hb D-Los Angeles, individuals with Hb G Coushatta may experience mild hemolytic anemia, but the clinical severity can vary.…”
Section: Hb G-coushatta [β22(b4) Glu→ala]mentioning
confidence: 99%
“…Hb G-Coushatta data associated with the [− + − + + + +] haplotype in Denizli, Türkiye have been published [4,29]. It has been reported that the Hb G-Coushatta cases in this region date back to 38,000 ybp [30]. Similar to Hb D-Los Angeles, individuals with Hb G Coushatta may experience mild hemolytic anemia, but the clinical severity can vary.…”
Section: Hb G-coushatta [β22(b4) Glu→ala]mentioning
confidence: 99%
“…Hemoglobin G-Coushatta with the preferred name NM_000518.4(HBB):c.68A>C (p.Glu23Ala) is an abnormal β-chain structural Hb caused by the substitution of the glutamyl group within residue at position 22 [β22 (B4)Glu →Ala] 3 . This type of Hb variant was identified in various countries, such as Japan, Algeria, Korea, Turkey, and Thailand 3 – 7 .…”
Section: Case Reportmentioning
confidence: 99%
“…HbG-Coushatta has the substitution of the negatively charged glutamyl group with a neutral alanine residue at position 22 3 . This replacement typically affects the distribution of charges and impairs molecular function.…”
Section: Case Reportmentioning
confidence: 99%